Geological risk affecting the village of Tapacocha (Recuay, Ancash) - Manrique, E. (2017)
Buildings standing on unstable soils are vulnerable to natural processes such as internal and external geodynamics and climate change. The village of Tapacocha, which is settled on slid floor, would be sensitive to those natural processes. The May 1970 earthquake caused ground fracture and building destruction; heavy rains in 1942 and 1997 caused mudslides that destroyed buildings and agriculture land. The internal geodynamics gave its shape to the base rocks through intense folding and fracturing of the sedimentary rocks; the external geodynamics created shapes through rotational movements, landslides and differential erosion. Presently, climate change is causing unusual torrential rains that periodically erode and threaten buildings and agriculture. The goal of this study is to advise the authorities and the population on ways to prevent and mitigate the destructive effects of these natural events.